SOCIAL SECURITY OF YESTERDAY AND TOMORROW – IN SEARCH OF THE WAY TO SOCIAL SECURITY (Research Bulletins of the Faculty of Economic Sciences, 2023)
In the author's publication, the study of systematization was published. The issue of connection with the formation of the modern social system. On the basis of specificity in various methods of shaping social security systems. In addition, some publications indicate how social insurance may develop in the future.
Keywords: Social security, Social insurance, Legal security